Rancang Bangun Sistem Minimarket Otomatis Berbasis IoT - Anjani, Ida Ayu Sri Sinta; Jasa, Lie; Agung, IGAP Raka (Majalah Ilmiah Teknologi Elektro, 2020)
In this era of globalization, developments occur in all aspects, one of which is the economy. One of the developments that occurred in the modern era was the emergence of minimarkets as shopping centers to replace markets. Minimarket provides convenient shopping facilities for customers. But minimarkets still have problems where there are long traffic jams on certain days or hours, thereby reducing the time efficiency of customers. Another problem that arises is that customers do not know the stock availability of the goods before coming to the minimarket. Therefore a system was developed that can check the availability of goods and make purchases automatically remotely. The system built using Arduino Mega and ESP as the brain tool, the sensors used are limit switches and IR sensors. The drives used in this study are the wiper motor as the x-axis driver and the power window motor as they drive. The servo motor is used as a driving force for the room door and for moving food to fall. In the study, the results obtained at the time of taking food were carried out 12 experiments in which the results of the tool could take food according to the input received from the application. In the experiment of taking goods, it was carried out with 12 experiments where it was found that the tool was able to take goods according to the input data received from the application and to the point of collection. The power consumption required in this design is 35.7 watts on standby, 42.84 watts when taking food, and 113.68 watts when the appliance is moving. Keyword— Aplikasi Android, Arduino Mega,ESP8266, Firebase, Minimarket.